The Natural History of Non-operatively Treated Traumatic Triangular Fibrocartilage Complex Tears: A Systematic Review - Choi, Seung Il; MacLean, Simon; Malik, Shabhaz (Journal of Wrist Surgery, 2024)
Purpose Operative treatment of triangular fibrocartilage complex (TFCC) tears has been well researched; however, data regarding nonoperative management is mixed and scarce. Our review aimed to utilize available data to formulate conclusions regarding treatment algorithms for this heterogeneous injury group.Methods A thorough literature review was performed in Medline (OVID), Embase, Cochrane Library, and PubMed databases with search terms including “triangular fibrocartilage complex” and variations on the full term including “triangular fibrocartilage” or “TFCC,” alongside “non-operative” and “conservative.” Results were then subject to inclusion criteria, ultimately identifying eight studies.Results The studies involved a total of 425 patients and 427 wrists for analysis. The mean age ranged from 30.7 years to 60.4 years. 53.6% of patients were male. The mean follow-up ranged from 12 months to 7 years, with an overall mean follow-up period of 27 months. Primary endpoints focused on various functional outcome scores, range of motion, grip strength, and pain. The nonoperative management of TFCC tears resulted in noninferior and comparable outcomes to operative management.Conclusion Our review identified that the nonoperative management of Palmer-type IB tears with a short period of above-elbow immobilization was an effective treatment option with good functional outcome scores. The nonoperative management of general TFCC tears resulted in comparable functional outcomes when viewed alongside results from other systematic reviews. Risk factors for developing a poor functional outcome or requiring operative management included distal radioulnar joint subluxation, short-arm immobilization, and full tears of the foveal attachment. However, further randomized controlled trials with homogenous data collection are required to make further conclusions regarding the management of this condition.
Keywords: Triangular fibrocartilage complex; TFCC; Nonoperative; Conservative